Analisis Manajemen Risiko pada UMKM Frozen Mas Isal di Kota Balikpapan - Wiwin Pebriana; Wiwik Saraswati; Nira Dewi Susanti; Diah Anggraini (Lembaga Teewan Journal Solutions, 2026)
This study examines the implementation of risk management at the Mas Isal Frozen Food UMKM in Balikpapan using a qualitative case study approach. Data were collected through interviews, observations, and document analysis to identify the main risks faced by the business, including financial, operational, and reputational risks. The results indicate that financial risks are related to cash management, expansion financing, and fluctuations in imported raw material prices; operational risks arise from limited raw material supplies, late deliveries, and labor shortages during peak periods; while reputational risks are related to product quality consistency, personal branding, and customer service effectiveness. The UMKM has implemented several mitigations such as the use of POS and expense recording, contracts with several distributors, cold chain maintenance, and employee incentives, but challenges such as price volatility, power outages, internal coordination, and potential fraud continue to impact business sustainability. Strategic recommendations are developed to improve operational resilience and reputation